2022
DOI: 10.1177/24730114211069080
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of MRI to Evaluate Acute Lisfranc Joint Injuries: Comparison With Direct Operative Observations

Abstract: Background: Early diagnosis is important in patients with Lisfranc joint injury to avoid subsequent complications. As the ligaments in the Lisfranc joint are relatively small and course obliquely, isotropic 3-dimensional (3D) magnetic resonance imaging (MRI) can be beneficial to evaluate ligament injury. The purpose of this study was to investigate the diagnostic accuracy of MRI, including isotropic 3D MRI for acute injury of the Lisfranc joint, especially of the interosseous C1-M2 ligament (Lisfranc ligament)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Kitsukawa et al reported that diagnoses of Lisfranc injury on MRI in oblique plane parallel to the ligament with isotropic 3D MRI reliably matched with direct intraoperative observations. 9 However, MRO is not a dynamic and weight-bearing imaging modality to show functional instability. Another study by Naguib et al, concluded that the accuracy of surgeons’ eye tracking assessment of intraoperative fluoroscopic imaging during stress examination of the tarsometatarsal joint complex in the diagnosis of Lisfranc injuries was reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitsukawa et al reported that diagnoses of Lisfranc injury on MRI in oblique plane parallel to the ligament with isotropic 3D MRI reliably matched with direct intraoperative observations. 9 However, MRO is not a dynamic and weight-bearing imaging modality to show functional instability. Another study by Naguib et al, concluded that the accuracy of surgeons’ eye tracking assessment of intraoperative fluoroscopic imaging during stress examination of the tarsometatarsal joint complex in the diagnosis of Lisfranc injuries was reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various imaging methods, intraoperative examination is the gold standard for confirmation of the diagnosis. 9,10 However, the intraoperative stress examination of the Lisfranc joint by applying a distraction force is not standardized and not a reproducible method. 11 Surgeons apply various amounts of force on the joint to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of Lisfranc injuries can be difficult as conventional radiographs of the foot will not show ligament subluxation nor subtle injuries, and as a result, treatment may be delayed, and the patient may suffer from prolonged pain, post-traumatic arthritis, and flat foot [ 6 - 8 ]. The sensitivity of conventional radiographs is only 84% [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI are some of the modalities that are used to assess TMTJ, which are superior to radiographs. CT scans can show uninterrupted images, and MRI is the gold standard modality as it visualizes soft tissues and ligamentous injuries [ 6 , 9 ]. It is documented that MRI has a sensitivity of 90% compared to intraoperative findings [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…4). If previous investigations have been normal and there is continuing concern regarding the injury, MRI is superior in revealing the so-called subtle injury 28,35,37,38 . Stress testing under anesthesia has been performed historically, but with advances in imaging, is now seldom used for diagnostic purposes, although commonly performed at the time of operative stabilization.…”
Section: Investigationsmentioning
confidence: 99%